RISE: Portal for research and innovation management PRIMe / Prof. Dr Nor Azura Md Ghani ... [et al.] - Md Ghani, Nor Azura; Suliman, Saiful Izwan; Abd Hamid, Umi Marshida; Musa, Khairunnisa; Ismail, Iwanie; Omar, Khairunnisa; A. Hamid, Nor Malini; Abd Rashid, Mohamad Rezduan; Othman, Norazlin; Khaizuan, Muhammad Afif (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
The University Executive Council Meeting (MEU Bill 31/2020 dated 6 October 2020) offered a university research grant for the purpose of UiTM Research Data Management System Development in collaboration with Universiti Teknologi Malaysia (UTM) as a consultant while Unit ICT, Office of Deputy Vice-Chancellor (Research & Innovation), UiTM become a strategic partner in the provision and maintenance.